2020
DOI: 10.1186/s12889-020-09385-y
|View full text |Cite
|
Sign up to set email alerts
|

An application of the theory of planned behavior to self-care in patients with hypertension

Abstract: Background: Self-care behaviors and positive changes in lifestyle are essential for successful hypertension control. We used a behavioral model based on the theory of planned behavior to assess which factors influence self-care behaviors for controlling hypertension. Methods: In this cross-sectional study, five hundred patients with at leastaone-year history of diagnosed hypertension participated in this study. The data collection tool was designed based on the theory of planned behavior. Structural equation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 29 publications
2
25
1
2
Order By: Relevance
“…In recent years, as the concept of health promotion and preventive medicine has become more popular, health behaviors and self-care management have become more important to the public. Therefore, the study of health behavior models will be important in designing effective interventions to improve self-health management [ 5 ]. The Theory of Planned Behavior (TPB) is a health behavior model that is widely used in the health care field.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, as the concept of health promotion and preventive medicine has become more popular, health behaviors and self-care management have become more important to the public. Therefore, the study of health behavior models will be important in designing effective interventions to improve self-health management [ 5 ]. The Theory of Planned Behavior (TPB) is a health behavior model that is widely used in the health care field.…”
Section: Introductionmentioning
confidence: 99%
“…Needs underlie behavioural intent, resulting in a specific health behaviour [ 48 ]. To examine normative and comparative needs, we will invite healthcare professionals involved into follow-up care to participate in focus groups.…”
Section: Methods / Designmentioning
confidence: 99%
“…In addition to the original domains of the TRA (attitude, attention and behavioural relationships), the TPB includes the indirect measurement of behavioural beliefs, normative beliefs and perceived behavioural control. Behavioural intention is a key determinant of the TPB, especially its influence on disease outcomes such as quality of life ( 18 ). Francis et al ( 19 ) suggested that attitude, subjective norms and perceived behavioural control, which are the domains representing health-related beliefs, can increase an individual’s likelihood of taking action.…”
Section: Methodsmentioning
confidence: 99%